Impact of galectin-3 on neurotrophic factor expression by PCR array: potential implications for the human cornea - Woodward, Ashley M.; Argüeso, Pablo (Frontiers in Cell and Developmental Biology, 2024)
The cornea is densely innervated to maintain the integrity of the ocular surface, facilitating functions such as sensation and tear production. Following damage, alterations in the corneal microenvironment can profoundly affect its innervation, potentially impairing healing and sensory perception. One protein frequently upregulated at the ocular surface following tissue damage is galectin-3, but its contribution to corneal nerve regeneration remains unclear. Here, we sought to delineate the role of galectin-3 in regulating the expression of neurotrophic factors by different human cell types. Using a pathway-focused PCR array, we first evaluated the expression of neurotrophic factors in primary cultures of human corneal epithelial cells and fibroblasts. We found that these cell types contributed differently to the expression of these factors, with fibroblasts exhibiting higher levels of nerve growth factor, brain-derived neurotrophic factor, and GDNF compared to epithelial cells. Treatment with exogenous galectin-3 did not significantly affect epithelial cells; however, it did lead to increased synthesis and secretion of IL6, a cytokine known to influence neuronal survival and modulate inflammatory responses, by corneal fibroblasts. Using the human-derived SH-SY5Y cell line as a neuron-like cell model, we also found that galectin-3 stimulated the expression of FOS and LIF, two genes involved in neural differentiation and survival. In summary, these in vitro findings suggest that the presence of galectin-3 in the corneal environment may influence the neuronal response to injury.